Analysis of magnetic resonance splectroscopy characteristics in patients with type 2 diabetes complicated with stroke - Wang, Yu; Wang, Ying; Peng, Gang; Liang, Wenwen; Chen, Jie; Chen, Kai; Yang, Xiaodan; Jiang, Jiehui; Huang, Bingcang (Frontiers in Medicine, 2022)
In this study, we investigated the metabolism of white matter by magnetic resonance spectroscopy (MRS) in stroke complicated with diabetes mellitus in combination with glycosylated hemoglobin (HbAlc) detection and clinical neurological deficit score (NIHSS). 53 patients with stroke within 24 hours after onset were collected and scanned by MRS. The biochemical, clinical and imaging characteristics of patients were analyzed. Patients were divided into 3 groups according to HbAlc levels: Good glycemic control (A): <6.5%; satisfactory glycemic control (B): 6.5% to 7.5% and poor glycemic control (C): > 7.5%. The results showed that HbA1c levels were positively correlated with NIHSS in patients with acute ischemic stroke (AIS). There is significant difference in NAA/Cr between the infarcted site of the three groups and the mirror site. HbA1C level was negatively correlated with NAA/Cr in patients with AIS, and there was no significant correlation between NIHSS score and NAA/Cr. The data above demonstrated that the MRS imaging can be used to explain the adverse effects of hyperglycated hemoglobin on brain parenchyma from the perspective of imaging. This imaging technique and clinical NIHSS score have a high consistency in evaluating stroke.